2010
DOI: 10.11609/jott.o1946.1392-400
|View full text |Cite
|
Sign up to set email alerts
|

Entomofauna of Kane Wildlife Sanctuary, Arunachal Pradesh, northeastern India

Abstract: prior permission to carry out the survey. Our appreciations are due to Mr. Tayeng Mize (DFO), Kane Wildlife Sanctuary and subordinate staffs for their tireless help during the survey trips. Thanks are also extended to Director, SFRI (Itanagar) and Dr. G. Srinivasan, Scientists-in-charge ZSI (Itanagar) for providing necessary assistances in insect identification. Our gratefulness are extended to Dr. Ch. Chitrpati Devi, Lecturer, D.M. College, Imphal for determining the identities of Collembolan insects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Beside this, seven species, viz., Nupserha nigriceps, Pterolophia (Hylobrotus) tuberculatrix, Neocerambyx grandis, Olenecamptus indianus, Obereopsis obscura obscura, Aristobia reticulator and Sarothrocera lowii are being reported from Arunachal Pradesh, northeastern India for the first time. The status of the new reports of the present study were confirmed by reviewing previously published literature of Zoological Survey of India (Sengupta & Sengupta 1981;Mukhopadhyay & Biswas 2000a, 2002bMukhopadhyay & Halder 2004;Anonymous 2006;Ramakrishna & Alfred 2006;Singh et al 2007), , Singh et al (2010), Agarwala & Bhattacharjee (2012), CAB abstracts, Catalogue of life and Zoological records. The known host plants and colour images of all the specimens have also been included in the present paper.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Beside this, seven species, viz., Nupserha nigriceps, Pterolophia (Hylobrotus) tuberculatrix, Neocerambyx grandis, Olenecamptus indianus, Obereopsis obscura obscura, Aristobia reticulator and Sarothrocera lowii are being reported from Arunachal Pradesh, northeastern India for the first time. The status of the new reports of the present study were confirmed by reviewing previously published literature of Zoological Survey of India (Sengupta & Sengupta 1981;Mukhopadhyay & Biswas 2000a, 2002bMukhopadhyay & Halder 2004;Anonymous 2006;Ramakrishna & Alfred 2006;Singh et al 2007), , Singh et al (2010), Agarwala & Bhattacharjee (2012), CAB abstracts, Catalogue of life and Zoological records. The known host plants and colour images of all the specimens have also been included in the present paper.…”
Section: Resultssupporting
confidence: 73%
“…Sengupta & Sengupta 1981 recorded 16 cerambycids from Arunachal Pradesh. Later eight species of longicorns were reported in West Siang of Arunachal Pradesh by Singh et al (2010). Several more species have been reported from India and adjacent countries (Holzschuh 1999(Holzschuh , 2003Ghate 2012;Agarwala & Bhattacharjee 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Singh et al reported 12 species of the family Scarabaeidae from 70 species of beetles (Coleoptera) in Kane Wildlife Sanctuary from Arunachal Pradesh. 38 59 species of scarabaeid beetles were collected in and around Amba Reserved forest of Western Ghat region Kolhapur district, Maharashtra by Aland et al 39 29 species of Scarabaeidae family was reported by Bhawane et al with most of them being polyphagous and serious pest. 40 He also reported 26 species of dung beetles belonging to Scarabaeinae subfamily from Sindhudurg district, Maharashtra.…”
Section: Indiamentioning
confidence: 99%